DEVELOPING A TASK-BASED ENGLISH FOR SPECIFIC PURPOSES (ESP) CURRICULUM FOR FIRST-YEAR MEDICAL STUDENTS: A COMMUNICATIVE APPROACH - Zaripbayeva Nasiba (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Medical students require specialized English language skills to engage effectively in their studies and future professional communication. This research explores the development of a task-based English for Specific Purposes (ESP) curriculum tailored for first-year medical students. By employing a needs analysis approach, the study identifies key language skills required in medical contexts, including patient communication, medical terminology, and academic writing. Task-based language teaching (TBLT) is proposed as a suitable pedagogical framework to enhance student engagement and language acquisition. The study contributes to the field of ESP by providing a structured curriculum that aligns with real-world medical communication needs.